Digital Marketing Research: Methods and Emerging Practices - Jayant Sharma, (AG Volumes, 2025)
This review will discuss the development, techniques and new practices of digital marketing research due to the rapid technological change and altering consumer behavior. It underscores the shift of the old-fashioned methods of research, which include surveys, interviews, and experiments, to data-driven methods such as web analytics, social media analytics, big data, and machine learning. The paper focuses on the increasing use of artificial intelligence, predictive analytics, influencer analysis, and neuromarketing in terms of improving personalization and decision-making. The data privacy, bias, and transparency concerns and ethical and methodological issues are also addressed, which makes the multidisciplinary and strategic importance of digital marketing research.